Jamadar Bapu Laxman Chowk - Ghosh, Ayan (2023)
Port Trust War Memorial is located on Jamadar Bapu Laxman Chowk, named after Bapu Laxman Lamkhade. He was the first Customs officer to be conferred the President’s Award in 1964, and again in 1979 (posthumously), for effecting a large number of opium seizures, gold, and counterfeit currency. Feared by smugglers, he was given the epithet 'Kohinoor of the Indian Customs'.